2022
DOI: 10.3390/ani12121515
|View full text |Cite
|
Sign up to set email alerts
|

Insects in Pet Food Industry—Hope or Threat?

Abstract: Due to the increasing global population, the world cannot currently support the well-known techniques of food production due to their harmful effects on land use, water consumption, and greenhouse gas emissions. The key answer is a solution based on the use of edible insects. They have always been present in the diet of animals. They are characterized by a very good nutritional value (e.g., high protein content and contents of essential amino acids and fatty acids, including lauric acid), and products with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 119 publications
0
11
0
2
Order By: Relevance
“…As summarized by Kępińska-Pacelik and Biel (2022) , while limited data exists published work suggests that incorporating insects as a portion of the diet for dogs does not negatively impact palatability, digestibility, or fecal consistency. In unpublished research from our group ( Kerr et al, 2020 ) preference testing of dried BSFL (microwave dried, unprocessed, and whole) compared to commercial dog treats (beef, lamb, pork, chicken, fish, or sweet potato products) indicated that dogs preferred the traditional protein sourced treats, although dogs were interested in the BSFL and some dogs preferentially selected insects (particularly when selecting between sweet potato or BSFL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized by Kępińska-Pacelik and Biel (2022) , while limited data exists published work suggests that incorporating insects as a portion of the diet for dogs does not negatively impact palatability, digestibility, or fecal consistency. In unpublished research from our group ( Kerr et al, 2020 ) preference testing of dried BSFL (microwave dried, unprocessed, and whole) compared to commercial dog treats (beef, lamb, pork, chicken, fish, or sweet potato products) indicated that dogs preferred the traditional protein sourced treats, although dogs were interested in the BSFL and some dogs preferentially selected insects (particularly when selecting between sweet potato or BSFL).…”
Section: Introductionmentioning
confidence: 99%
“…This was a small masters research experiment and did not attempt to quantify the previous food experiences of the dogs tested and was further limited by the comparison of processed traditional proteins compared to whole unprocessed BSFL. Consumer acceptance of insects in pet feed is a larger barrier but many owners do show interest in feeds containing insects and it is likely that exposure and education can increase consumer demand for such products ( DiGiacomo et al, 2019 ; Kępińska-Pacelik and Biel, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Feed insects can serve as a substitute for traditional feed ingredients, and they may serve as alternatives to grain feed such as soybean and corn, as well as fishmeal ( Nogales-Mérida et al, 2018 ; van Raamsdonk et al, 2017 ). In the feed market especially, there has been a trend towards reducing the proportion of soybeans used in feed by establishing mixing ratios because of the decrease in crop production caused by global warming ( Boerema et al, 2016 ; Kępińska-Pacelik and Biel, 2022 ). Edible insects are also being considered fishmeal substitutes in feed because of the scarcity of fishery resources and to reduce feed costs.…”
Section: Introductionmentioning
confidence: 99%
“…These include larvae of the black soldier fly ( Hermetia illucens ), mealworm ( Tenebrio molitor ), supermealworm ( Zophobas morio ), housefly ( Musca domestica ), and crickets ( Acheta domesticus ; van Raamsdonk et al, 2017 ). They are being developed into feed products for various animals such as pigs ( Ji et al, 2016 ; Veldkamp and Bosch, 2015 ), poultry ( Cullere et al, 2018 ; Pieterse et al, 2019 ), fish ( Nogales-Mérida et al, 2018 ; Zarantoniello et al, 2020 ), and are even used in pet food ( Kępińska-Pacelik and Biel, 2022 ). The possibility of using them as cattle feed has also been discussed ( Drewery et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation